Delayed diagnosis of hemoptysis in the case of prior aortic coarctation repair: A case report of aortobronchial fistula - Vinay Kansal; Sudhir Nagpal (Respiratory Medicine Case Reports, 2015)
We report a case of a 46-year old man who presented with spontaneous bright red blood per mouth for several months. The patient had history of aortic coarctation repair at age 17. Endoscopy and nasopharyngeoscopy revealed no source of bleeding. Computed tomography scan revealed the presence of thoracic aortic pseudoaneurysm with the formation of an aortobronchial fistula (ABF). This case illustrates the high index of suspicion for ABF in the case of hemoptysis or hematemesis with prior history of coarctation repair. Furthermore, we discuss the role of thoracic endovascular aneurysm repair (TEVAR) as the standard of repair over open surgery.